The legacy of Ruth Klüger and the end of the Auschwitz century - Gelber, Mark H. 1951- (Perspectives on Jewish texts and contexts, 2022)
Ruth Klüger (1931 - 2020) passed away on October 5, 2020 in the U.S. Born in Vienna and deported to Theresienstadt, she survived Auschwitz and the Shoah together with her mother. After living in Germany for a short time after the War, she immigrated to New York. She was educated in the U.S. and received degrees in English literature as well as her Ph.D. in German literature at the University of California, Berkeley. She taught at several American universities. She has numerous scholarly publications to her credit, mostly in the fields of German and Austrian literary history. She is also recognized as a poet in her own right, an essayist, and a feminist critic. She returned to Europe, where she was a guest professor in Göttingen and Vienna. Her memoir, entitled weiter leben (1992), which she translated and revised in an English parallel-text as Still Alive, was a major bestseller and highly regarded autobiographical account of a Holocaust survivor.